Policy Recommendations for Handling Brain Drains to Provide Sustainability in Emerging Economies - BAŞ, HALİM (My University, 2022)
The purpose of this study is to identify the most significant issues to handle brain drains to provide sustainability in emerging economies. In this framework, a new model has been created that consists of two different stages for this situation. Firstly, necessary criteria are identified based on the key items of the balanced scorecard approach. These factors are weighted by using a bipolar q-rung orthopair fuzzy multi stepwise weight assessment ratio analysis (BOFQ M-SWARA) approach with golden ratio. Next, seven emerging economies are ranked with respect to their performance in decreasing brain drains by BOFQ, the elimination and choice of translating reality (ELECTRE) with the golden ratio. An evaluation is also carried out with intuitionistic fuzzy sets (IFSs) and Pythagorean fuzzy sets (PFSs) to test the validity of the findings. The results are similar for all different fuzzy sets, which indicates that the findings are quite coherent and reliable. The most important factor in reducing brain drain has been identified as technical competency. It would be appropriate for countries to provide tax exemptions for research and development studies. This situation can easily attract the attention of companies, as it will contribute to the reduction of costs. Thus, it will be easier to provide technological innovations in the country in the future. Thanks to technological development, it is possible to increase the productivity of enterprises in the country. In this way, the brain drain problem can be minimized as qualified personnel stay in the country. With the high number of qualified people in the country, it will be possible to produce eco-innovative products and develop clean energy technology. Due to this issue, sustainability can be provided in the economic development of emerging economies.Keywords:sustainability;economic development;brain drain;emerging economies
Keywords: Sosyal ve Beşeri Bilimler; Çalışma Ekonomisi ve Endüstri ilişkileri; Social Sciences and Humanities; Labor Economics and Industrial Relations; Sosyal Bilimler (SOC); Ekonomi ve İş; ENDÜSTRİYEL İLİŞKİLER VE ÇALIŞMA; Social Sciences (SOC); ECONOMICS & BUSINESS; INDUSTRIAL RELATIONS & LABOR; Endüstriyel ilişkiler; Sosyal Bilimler ve Beşeri Bilimler; Industrial Relations; Social Sciences & Humanities; sustainability; economic development; brain drain; emerging economies